STATUS FISIOLOGIS SAPI SUMBA ONGOLE (Bos indicus) DI KAWASAN PEMBIBITAN SAPI PULAU SUMBA - Gaina, Cynthia Dewi; Sanam, Maxs U. E.; Foeh, Nancy D. F. K.; Tophianong, Tarsisius Considus; Nalley, Wilmientje Marlene-Mesang; Benu, Imanuel (JURNAL KAJIAN VETERINER, 2021)
Physiological status is an indicator to determine the degree of health and productivity of livestock. This study aims to identify the physiological status of Sumba Ongole (SO) beef cattle on the island of Sumba by measuring body temperature, respiration frequency, pulse, and body conditioning score (BCS). Overall, there were 70 cows used in the study. Based on gender, there were 21 bulls and 49 cows and they were classified based on age, there were 3 categories, 1-1.5 years, 2-2.5 years, and 3 years. The parameters measured were body temperature, respiratory rate, pulse frequency, and BCS. The results of the study which were processed using analysis of variances (ANOVA) showed that there was no effect of sex or age on body temperature, respiration frequency, pulse frequency (P> 0.05), but there was a significant difference in the age category with the body score of SO cattle (P<0.05). It could be concluded that the physiological status of SO beef cattle which includes body temperature, respiration frequency, and pulse frequency does not show a significant effect on both sex and age, but there is a significant difference in the body score of cattle based on age categories. This research data could probably be used later as a reference for maintaining the health management of SO beef cattle to achieve optimal productivity and profitability.